The importance of the family in psychiatric treatment (Research, Society and Development, 2023)
The family plays an important role in the treatment of psychiatric patients, as they are overburdened with caring for patients with mental disorders. Objective: This article aims to address the importance of the family in the treatment of psychiatric patients. Methodology: An integrative review was used, based on previously published scientific papers on the subject under study. The following descriptors were used: family; treatment; psychiatric patient. Results: Among the articles selected for the integrative review, it was found that all positively highlight the family role in treatment in general for patients with differential diagnoses of mental health disorders. Nonetheless, many articles still address the difficulties that this support network brings with it, while aiming for ways of raising awareness and tools that keep family and patient interaction going. Conclusion: The participation of the family is indispensable in the care and treatment of patients with mental disorders, as it encourages them to follow treatment, welcomes them appropriately and includes them in society.